Seasonal variation of microsporidia MB infection in Anopheles gambiae and Anopheles coluzzii in two different geographical localities in Benin - Tchigossou, G.; Lontsi-Demano, M.; Tossou, E.; Sovegnon, P.M.; Akoton, R.; Adanzounon, D.; Dossou, H.; Koto, M.; Ogbon, E.A.; Gouete, M.; Nattoh, G.; Djouaka, R.F. (2025)
Microsporidia MB, a naturally occurring Anopheles symbiont was shown to strongly impair Plasmodium transmission without imposing deleterious fitness effects on larval development, fecundity, adult survival, and adult sex ratio, and for these reasons it is being proposed as a promising tool for malaria control. However, there is a limited knowledge about its ecology, transmission dynamics in the environments with varying abiotic conditions, and whether these could impact on the mode of host transmission. This study aimed to determine the presence and prevalence of Microsporidia MB in rice fields in Benin during both the dry and wet seasons.